Funções de memória após lobectomia temporal anterior e amigdalohipocampectomia seletiva : um estudo comparativo - Azambuja, Luciana Schermann (2005)
Objective: To compare the neuropsychological effects of anterior temporal lobectomy (ATL) and selective amygdalohippocampectomy (AH) on memory tests, and to determine which variables are correlated with post-operative memory deficits.Methodology: It was compared changes in neuropsychological scores in 154 patients who underwent temporal lobe epilepsy due hippocampal sclerosis (ATL n= 63 or AH n=91). We assessed decline in memory as measured by the Weschler Memory Scale-Revised (WMS-R), and Rey Verbal Auditory Learning Test (RAVLT). Deriving logistic regression equation was used to the following measures variables: type of surgery, seizure outcome, age onset, manual dominance, side of resection, timing of postoperative assessment and level of education.Results: No differences were found on memory immediate recall (logical memory and visual reproduction) between patients who underwent ATL or AH (p>0,05). On the other hand, the delayed recall presented a significant decrease after ATL on verbal (p=0,007) and visual memory test (p=0,03). Better verbal memory performance showed higher risk of suffering post surgery decrease, but this association was not observed on visual memory scores. Losses in verbal memory were higher after left side surgery. Visual memory was founded independent of the side of resection. No specific association was detected between memory performance after surgery and age at onset seizure, seizure control, manual dominance and timing of postoperative assessment. These findings evidence that lower level of education was associated with memory and learning impairment after both type of surgery.Conclusion: Losses on delayed recall both verbal and visual memory tests were increased after LTA than AH. Left temporal lobe excisions showed a negative impact on verbal memory, but decrease on visual memory after right temporal lobe resection was not observed. Better performance on verbal memory test on presurgical assessment is at higher risk of suffering post surgery decrease.